Developing research priorities for nurses working in the gynaecology setting in Western Australia - Bosco, Anna; Williams, N.; Graham, J.; Malagas, D.; Hauck, Y. (Elsevier BV, 2016)
Background: Nurses working in clinical settings are instrumental to translating research into practice. The Delphi approach has been used by clinicians worldwide to set research agendas relevant to their clinical work. Aim: To identify nursing research priorities at the tertiary women's hospital in Western Australia and to develop an agenda for gynaecological nursing research. Methods: A three-round Delphi study was used. Round one incorporated an open-ended questionnaire to generate ideas or issues important to gynaecology nurses. During round two, the 32 topics generated from the first round were prioritised into 12 topics with a final ranking performed in round three. Findings: Fifty-four nurses who work in gynaecology clinical areas at the study hospital were invited to participate with 18 (33.3%) participating in round one, 41 (75.9%) in round two and 40 nurses (74.1%) in the final round. The highest ranked research priorities were: managing trial of void; providing compassionate care to women who experience pregnancy loss - the role of the gynaecological nurse; and understanding a woman's journey of treatment following a diagnosis of gynaecological cancer. Discussion: We explore potential factors from the literature around the identified gynaecology research topics plus challenges around the generation and translation of evidence into clinical practice. Conclusion: Establishing a partnership between researchers and gynaecology nurses has contributed to the development of a nursing research agenda. We anticipate that using the Delphi approach may facilitate future collaboration in implementing this research agenda and translating the findings into clinical practice.